Apparent hypoxic changes in pulmonary arterioles and small arteries in infancy. - Kendeel, S R (1977)
The pulmonary arterioles and small arteries were studied and their musculature and its nuclei were quantified in 90 neonates, infants, and young children who had suffered from a variety of clinical and hypoxic conditions immediately before death. Among the 90 cases investigated in this study, 30 were of sudden infant death syndrome (SIDS). No evidence was found to support the view that cases of SIDS are subjected to chronic hypoxia before death as significantly more medial muscle tissue in the pulmonary arterioles and small arteries was found in the chronic hypoxic group compared to the SIDS, non-hypoxic, and acute hypoxic groups. Furthermore, there was no statistically significant difference in the amount of medial muscle tissue of the pulmonary vessels as between the SIDS, non-hypoxic, and acute hypoxic groups. With other signs of acute hypoxia found at the necropsy of SIDS, the results of this study could be considered to support the view that cases of SIDS succumb as a result of an acute episode of hypoxia, or possibly repeated short-duration episodes of acute hypoxia which do not produce pulmonary vascular changes.